Desain Jaringan RT/RW Net Hotspot Sistem Dengan Mikrotik Routerboard Sebagai Manjemen Billing Implementasi Sistem Voucher Quota Di Lingkungan Pringsewu Selatan - Eko Hendrawan; Ahmad Aldi Saputra (Institut Bakti Nusantara, 2021)
This research is oriented towards the RT /RW Net Hotspot System Network Design with the Mikrotik Router Board as Billing Management for the Implementation of the Quota Voucher System using the Usermanager Tools. Utilization of User Manager Tools on Mikrotik which functions as a network user manager, with this User Manager Tools the admin can easily create voucher keywords with the generate system without manual inputting of keywords, this User Manager tool can only be accessed by administrators and accessed via computer devices. This system certainly makes it very easy for the Admin to manage user management. Clients can enjoy hotspot system internet access by purchasing a Hotspot Quota Voucher that has been determined according to user needs. With the hotspot system, it can make it easier for clients to reach internet access with the Hotspot Quota Voucher system.